The Cambridge Greek lexicon - Diggle, James; Fraser, Bruce Lovat; James, Patrick; Simkin, Oliver Benedict; Thompson, A. A.; Westripp, Simon J. (Cambridge University Press, 2021)
The Cambridge Greek Lexicon is based upon principles differing from those of existing Greek lexica. Entries are organised according to meaning, with a view to showing the developing senses of words and the relationships between those senses. Other contextual and explanatory information, all expressed in contemporary English, is included, such as the typical circumstances in which a word may be used, thus giving fresh insights into aspects of Greek language and culture. The editors have systematically re-examined the source material (including that which has been discovered since the end of the nineteenth century) and have made use of the most recent textual and philological scholarship. The Lexicon, which has been twenty years in the making, is written by an editorial team based in the Faculty of Classics in Cambridge, consisting of Professor James Diggle (editor-in-Chief), Dr Bruce Fraser, Dr Patrick James, Dr Oliver Simkin, Dr Anne Thompson, and Mr Simon Westripp